Effect of nitrogen doping on the electrochemical performance of resorcinol-formaldehyde based carbon aerogels as electrode material for supercapacitor applications. (15th April 2019) - Mirzaeian, Mojtaba; Abbas, Qaisar; Gibson, Des; Mazur, Michal
Abstract: Nitrogen doped resorcinol/formaldehyde carbon aerogels with controlled nitrogen content are synthesized by controlling the resorcinol/melamine molar ratio (R/M) during the synthesis of aerogel precursors. The carbons were used as electrode materials in an electrochemical capacitor using 6 M KOH solution as electrolyte. All samples exhibited amorphous structure with low degree of graphitization. The maximum specific capacitance of 208 Fg -1 was observed after doping of the carbon with nitrogen at R/M = 80. Drop in solution and charge transfer resistances from 0.57Ω to 0.15Ω and 0.05Ω–0.04Ω was also observed respectively, with the drop in contact angles from 123° to 103° for the carbon doped with nitrogen at R/M = 80. BET results showed that the pore volume and surface area of carbon increase after N-doping, with a BET surface area of 841 m 2  g −1 at R/M = 80. This R/M ratio is an optimum ratio at which incorporation of nitrogen into the carbon matrix improves the capacitive performance of cell as a result of improved porosity/wettability/conductivity/active sites of the electrode. Doping at higher nitrogen concentrations (R/M < 80) decreased the specific capacitance of the cell significantly due to decreased conductivity of carbon and suppression of the hopping rate of dopant. Graphical abstract: Image 1078 Highlights: Nitrogen doped resorcinol/formaldehyde carbon aerogels with controlled nitrogen content are synthesized. The contact angle of carbon and 6 M KOH solution dropped significantly from 123° to 103° after nitrogen doping. The best specific capacitance of 208 Fg -1 is obtained for the carbon doped with nitrogen at an R/M ratio of 80. The solution resistance dropped significantly from 0.57Ω to 0.15Ω after N- doping at an R/M ratio of 80. R/M ratio of 80 is the optimum R/M ratio at which nitrogen doping results in superior performance of the cell.